107 pupils received school supplies donated by UMP Alumni and NGOs - Aminatul Nor, Mohamed Said (2019)
A total of 107 pupils around Kuantan excitedly choose their school clothes and supplies at the Pusat Pakaian Hari-Hari in Kuantan for the upcoming school session.